A Model For Collaborative Creation And Ownership Of Digital Products - Chirema, Takunda (School of Economics, 2023)
This thesis presents Axone, a system that enables decentralized collaborative creation of digital products through interconnected digital content blocks. Axone provides the provenance of a digital product by storing its history since creation in an immutable Directed Acyclic Graph (DAG) data structure. This history comprises digital content blocks used in its creation, including how they referenced each other in the development of the final digital product. Through referencing, credit attribution is achieved and royalty fees due to the referenced content block are recorded and enforced. Content creators can concurrently work on a succeeding content block to produce various versions of unique digital products from the same original content block. Axone focuses on written work enabling different authors to contribute to a book (the digital product) in the form of chapters (digital content blocks), until its completion. Axone uses blockchain technology and web monetization to provide provenance for each chapter and to stream payments to authors.